Weaving Hope to Achieve Dreams Through Literacy: Literacy Assistance and Academic Guidance for Refugee Children at Yppgi Napua Primary School, Highlands Papua - Sepling Paling; Nurita Angesti Rahayu; Rita Sari; Arniati Kogoya; Jesterlin Tristianti Papendang; Agustina Kosay; Yosina Heluka; Yafli Ebzan Karoba; Ali Peyon; Nince Wakey Wenda; Helena Pekey; Vince Wanimbo (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Children are a nation's valuable asset and must be continuously educated and guided, both academically and in terms of character development. Among the children who require special attention are the refugee children from Nduga District, who are pursuing primary education at YPPGI Napua Primary School. The primary issue they face is their low literacy skills in reading, which negatively affects their academic abilities and further limits their ability to follow lessons, ultimately impacting their overall learning outcomes. Therefore, this community service program aims to train and guide refugee students at YPPGI Napua Primary School, Highlands Papua, who struggle with literacy and academic skills. The method used in this program is based on a participatory approach, where each student is provided with guidance tailored to their abilities and needs through five stages: Initial Coordination and Preparation, Pretest and Student Grouping, Reading and Academic Tutoring, Posttest and Progress Evaluation, and Advanced Learning and Final Testing. The results showed a significant improvement in reading ability and academic understanding. The final test conducted at the end of the program indicated that around 85% of the students made substantial progress. In conclusion, the literacy and academic tutoring program for refugee students at YPPGI Napua Primary School successfully achieved its primary goal of improving students' literacy and academic knowledge, and had a positive impact on their motivation and self-confidence in facing exams and advancing to junior high school. This program made a significant contribution to the development of education in the refugee area and could serve as an effective solution for improving education quality in remote regions, offering inspiration for the implementation of similar models in other areas facing similar challenges.